2019
DOI: 10.1590/0034-7167-2018-0291
|View full text |Cite
|
Sign up to set email alerts
|

Literacy in health and self-care in people with type 2 diabetes mellitus

Abstract: Objective: To evaluate the effect of educational intervention in the adherence to self-care activities and functional health literacy and numeracy in people with type 2 diabetes mellitus. Methods: This was a quasi-experimental study conducted in two units of the Brazilian Family Health Strategy, involving people with diabetes. Educational interventions occurred in three meetings, weekly, lasting 60 minutes on average. Data were collected using the Questionário de Autocuidado com o Diabetes, before and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 26 publications
(30 reference statements)
1
16
0
10
Order By: Relevance
“…This result corroborates with other national studies developed with different designs, but with the same self-care assessment tool [10] [22] [52]. The study conducted in the state of Piauí, Brazil, mentioned earlier [25], showed a low adherence to the item "taking insulin injections as recommended", within the "medication" dimension. Adherence to DM drug treatment varies widely in the literature, which reinforces the need for further research on this topic.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This result corroborates with other national studies developed with different designs, but with the same self-care assessment tool [10] [22] [52]. The study conducted in the state of Piauí, Brazil, mentioned earlier [25], showed a low adherence to the item "taking insulin injections as recommended", within the "medication" dimension. Adherence to DM drug treatment varies widely in the literature, which reinforces the need for further research on this topic.…”
Section: Discussionsupporting
confidence: 89%
“…In general, the sociodemographic, clinical and treatment characterization resembled that of other Brazilian population samples of people with DM [8] [25].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Para mensurar os resultados das intervenções, em oito dos 10 artigos houve a utilização de algum tipo de medidor de mudança de comportamento e autocuidado. Os mais utilizados foram o QAD -Questionário de Autocuidado em Diabetes (Marques et al, 2019;Moura et al, 2019;Imazu et al, 2015) e o DKN-A -Questionário de conhecimento do Diabetes (Figueira et al, 2017;Maia et al, 2016;Imazu et al 2015). Além desses, ainda houve a utilização do PAID -Questionário de Impacto na Qualidade de Vida em Diabetes (Imazu et al, 2015), ESM e DES-SF -Questionário de empoderamento para o DM2 (Macedo et al, 2017), MAT -ADOs e MAT -Insulina (Figueira et al, 2017).…”
Section: Metodologia/intervenção Número De Vezes Usadasunclassified
“…3.1 PERFIL SOCIAL E SUA RELAÇÃO COM O NÍVEL DE LETRAMENTO EM SAÚDE E PREVENÇÃO DE CÂNCER DE COLO DE ÚTEROCinco dos estudos identificaram de forma mais expressiva que os diferentes níveis socioeconômicos e de escolaridade estão diretamente relacionados com o nível baixo de letramento em saúde e acerca dos meios de prevenção do câncer do colo do útero.SegundoStrohl et al (2014), 73% de uma população de 215 afroamericanas revelaram conhecimentos insuficientes sobre o assunto, mesmo 87% dessa população tendo um nível de escolaridade de ensino médio ou superior e 93% dos participantes relacionando corretamente um desenho ao colo do útero, apenas 33% destes foram capazes de relacionar que o exame de papanicolau é realizado no colo do útero. Sendo que, 67%, do total, tinha ciência da existência de uma vacina contra HPV mas, apenas 37% relacionaram o vírus ao câncer e apenas 32%, da amostra total, poderia custear a vacinação, mas, apenas 28% das que tinham filhos ofertaram vacina contra HPV.Evidenciando que, mesmo tendo um nível de educação mediano a alto, as condições socioeconômicas da população estiveram diretamente relacionadas aos fatores de prevenção e o conhecimento dos mesmos.É imprescindível que as equipes de saúde desenvolvam atividades educativas que atendam a demanda de necessidade de educação em saúde da população, não somente abordando doença, mas que sejam intervenções realizadas de maneira contínua(MOURA et al 2019).Questão corroborada porYanikkerem et al (2012), em uma pesquisa concluída com 1036 participantes em uma cidade da Turquia em que 30,4% destes tinham recebido educação primária e 69,3% afirmaram que a renda familiar é proporcional as despesas, comprovou-se, que as mulheres com maior nível de escolaridade e econômia definiram, em geral, os fatores de risco para câncer de colo do útero de forma mais eficaz que as demais. Das que afirmaram conhecer o câncer do colo do útero (64,4%), apenas 19,5% delas tiveram conhecimento através dos profissionais de saúde e somente 2% através da escola, destas 688 mulheres, 37,2%(256)tinham um conhecimento baixo e apenas 17% (117) tinham um conhecimento considerado excelente.…”
unclassified